1982
DOI: 10.1128/jvi.42.2.519-529.1982
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Sequence of the Akv env Gene

Abstract: The sequence of 2,191 nucleotides encoding the env gene of murine retrovirus Akv was determined by using a molecular clone of the Akv provirus. Deduction of the encoded amino acid sequence showed that a single open reading frame encodes a 638-amino acid precursor to gp70 and p15E. In addition, there is a typical leader sequence preceding the amino terminus of gp70. The locations of potential glycosylation sites and other structural features indicate that the entire gp70 molecule and mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
112
0

Year Published

1983
1983
1990
1990

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(118 citation statements)
references
References 54 publications
6
112
0
Order By: Relevance
“…1 of the AKR-623 LTR (nucleotides 1 to 144 and 7,825 to 8,374) is identical to that reported by Van Beveren et al (56). Lenz et al (21) have reported the nucleotide sequence of the AKR-623 enm' gene (nucleotides 5,674 to 7,865). The sequence shown in Fig.…”
Section: 'Gcgccagtcctccgatagactgagtcgcccgggtacccgtgtatccaataaagcctttsupporting
confidence: 83%
See 3 more Smart Citations
“…1 of the AKR-623 LTR (nucleotides 1 to 144 and 7,825 to 8,374) is identical to that reported by Van Beveren et al (56). Lenz et al (21) have reported the nucleotide sequence of the AKR-623 enm' gene (nucleotides 5,674 to 7,865). The sequence shown in Fig.…”
Section: 'Gcgccagtcctccgatagactgagtcgcccgggtacccgtgtatccaataaagcctttsupporting
confidence: 83%
“…RNase T, oligonucleotides (23) and features discussed in the text are indicated below the sequence. identify any differences from the sequences of this region previously reported (15,21,56).…”
mentioning
confidence: 50%
See 2 more Smart Citations
“…The minor transmembrane protein (TM) has several functions, including binding to the SU protein, anchoring both envelope proteins to the virion surface via a membrane-spanning segment near the COOH terminus, and fusing viral and cellular membranes to allow entry of the virion core into the cytoplasm. This latter function is probably mediated by a group of hydrophobic residues near the NH2 terminus (3). These and other functional domains of the envelope proteins may also influence the pathogenicity of certain retroviruses .…”
mentioning
confidence: 99%